Protective Potential of Sodium-Glucose Cotransporter 2 Inhibitors in Internal Medicine (Part 2) - Ashot A. Avagimyan; Mohammad Sheibani; Artem I. Trofimenko; Evgenii E. Lysov; Farida M. Khamidova; Anahit Z. Aznauryan; Lilit M. Sukiasyan; Karmen T. Sahakyan; Tamara R. Gevorgyan; Marina R. Tatoyan; Gayane L. Mkrtchyan; Goharik L. Meltonyan; et al. (Инновационная медицина Кубани)
Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are now uncovering new possibilities in the field of internal medicine owing to their diverse protective effects. In the second part of the literature review, we explore potential applications of SGLT2i in hepatology, neurology, ophthalmology, and oncology, mechanisms of action of such drugs as dapagliflozin, empagliflozin, canagliflozin, etc, and their effect on different organs and systems.